(3GdChRGf hGdCcGjjd GdWHjI (B((3ef cJGH CbQGHGPGjf GdYfJQi(B)s ((3LQLS Hf GdMcje jhMfG GdeJfjM s)
(3ChdgG (B:s
(3GYde Cf GdQWd GdYQHj GKfG YTQ ChbjI, hGdChbjI YTQI OQGge, hgh GdQWd GdYQGbj, hGdef eGFJGf hSJhf OQgekG, hbO KHJ aj gPG GJaGb GdfGS hdfPcQ HYO Pdc GdChRGf GdWHjI CeG GdbjQGW abO YQaJ Cfg CQHY TYjQGJ s
(3BNQgG (B:s
(3eHJhQ GdBNQ, hBNQ GdehLhO efg(B: (3hCeG Gdcjd agh efGSHI Hjf cjd hCbQGfg hgh jfbSe bSejf(B: (3efg eG jSJYed aj GdLhGgQ GdjGHSI, hefg eG jSJYed aj GdLhGgQ GdQWHI, hGdeSJYed aj GdLhGgQ GdjGHSI s
(3Vef eLehY s
(3ef cJGH CbQGHGPjf GdYfJQjs
(3hGdYfJQj gh CHhGdeDjO eMeO Hf GdeLdj Hf GdUGFZ GdLRQj GdYfJQjs
(3hGdeJhai fMh SfI (B570 (3g` GdCYdGe (B241/7s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B32 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs